Toward Evidence-Based Practice. Issue 4 (July 2020) - Rohan, Annie J.; Breman, Rachel Blankstein; Capitulo, Kathleen Leask; O'Brien-Abel, Nancy
Abstract : Experts suggest how 6 research articles can be used in nursing practice.